Preventing intangible technology transfer (ITT) on the Internet and telecommunications for bioterrorism through Malaysia's Strategic Trade Act 2010 (STA 2010) - Abdul Majid, M.; Baharuddin, A.; Chang, L.W. (Elsevier, 2016)
Malaysia's Strategic Trade Act 2010 (STA 2010) was drafted to address export controls and associated trade controls such as transit, transhipment and brokering in the fulfilment of the Biological and Toxin Weapons Convention (BTWC), Chemical Weapons Convention (CWC), Non-Proliferation Treaty (NPT) and the United Nations Security Council (UNSC) Resolution 1540, which broadly address the proliferation of nuclear, biological and chemical weapons. Terrorists have been known to utilise websites and emails to place manuals, instructions, blueprints and other documents, known as Intangible Technology Transfer (ITT), to incite and encourage their peers to create biological weapons; subsequently, to launch an attack of bioterrorism. Simultaneously, terrorists may camouflage their identity and attend oral and visual exchanges such as teleconferences, virtual meetings and skills training sessions that disseminate relevant information on biological weapons. This makes it possible for terrorists who already possess some background knowledge of biological weapons to further their interests in creating these weapons. The objective of this study is to analyse Malaysia's STA 2010 concerning relevant provisions that are able to address the threat of ITT over the internet and telecommunications by terrorists in the context of disseminating knowledge of biological weapons to perpetuate bioterrorism. The results show that the provisions of Sections 2, 4, 9 and 10 of STA 2010 are relevant in addressing the ITT of individuals using the internet to encourage creating biological weapons abroad by involving extraterritorial jurisdiction, extradition and mutual assistance in criminal matters. This study concludes that Malaysia's Ministry of International Trade and Industry (MITI) and the Malaysian Communications and Multimedia Commission (MCMC), implementers of the STA 2010, must deliberate on these unclear matters and draft detailed guidelines to direct Malaysian researchers and academics, learning from the examples of other countries.